Life‐history plasticity and sustainable exploitation: a theory of growth compensation applied to walleye management. Issue 1 (1st January 2014) - Lester, Nigel P.; Shuter, Brian J.; Venturelli, Paul; Nadeau, Daniel
Abstract : A simple population model was developed to evaluate the role of plastic and evolutionary life‐history changes on sustainable exploitation rates. Plastic changes are embodied in density‐dependent compensatory adjustments to somatic growth rate and larval/juvenile survival, which can compensate for the reductions in reproductive lifetime and mean population fecundity that accompany the higher adult mortality imposed by exploitation. Evolutionary changes are embodied in the selective pressures that higher adult mortality imposes on age at maturity, length at maturity, and reproductive investment. Analytical development, based on a biphasic growth model, led to simple equations that show explicitly how sustainable exploitation rates are bounded by each of these effects. We show that density‐dependent growth combined with a fixed length at maturity and fixed reproductive investment can support exploitation‐driven mortality that is 80% of the level supported by evolutionary changes in maturation and reproductive investment. Sustainable fishing mortality is proportional to natural mortality ( M ) times the degree of density‐dependent growth, as modified by both the degree of density‐dependent early survival and the minimum harvestable length. We applied this model to estimate sustainable exploitation rates for North American walleye populations ( Sander vitreus ). Our analysis of demographic data from walleye populations spread across a broad latitudinal range indicates that density‐dependent variation in growth rate can vary by a factor of 2. Implications of this growth response are generally consistent with empirical studies suggesting that optimal fishing mortality is approximately 0.75 M for teleosts. This approach can be adapted to the management of other species, particularly when significant exploitation is imposed on many, widely distributed, but geographically isolated populations.